A longitudinal study to identify the influence of quality of chronic care delivery on productive interactions between patients and (teams of) healthcare professionals within disease management programmes. Issue 9 (19th September 2014) - Cramm, Jane Murray; Nieboer, Anna Petra
Abstract : Objective: The chronic care model is an increasingly used approach to improve the quality of care through system changes in care delivery. While theoretically these system changes are expected to increase productive patient–professional interaction empirical evidence is lacking. This study aims to identify the influence of quality of care on productive patient–professional interaction. Setting: Longitudinal study in 18 Dutch regions. Participants: Questionnaires were sent to all 5076 patients participating in 18 Disease Management Programmes (DMPs) in 2010 (2676 (53%) respondents). One year later (T1), 4693 patients still participating in the DMPs received a questionnaire (2191 (47%) respondents) and 2 years later (in 2012; T2) 1722 patients responded (out of 4350; 40% response). Interventions: DMPs Primary outcome measure: Patients' perceptions of the productivity of interactions (measured as relational coordination/coproduction of care) with professionals. Patients were asked about communication dimensions (frequent, accurate, and problem-solving communication) and relationship dimensions (shared goals and mutual respect). Findings: After controlling for background characteristics these results clearly show that quality of chronic care (T0), first-year changes in quality of chronic care (T1—T0) and second-year changes in quality of chronic care (T2—T1) predicted productive interactions between patients and professionals at T2 (all at p≤0.001). Furthermore, we found a negative relationship between lower educational level and productive interactions between patients and professionals 2 years later. Conclusions: We can conclude that successfully dealing with the consequences of chronic illnesses requires proactive patients who are able to make productive decisions together with their healthcare providers. Since patients and professionals share responsibility for management of the chronic illness, they must also share control of interactions and decisions. The importance of patient-centeredness is growing and this study reports a first example of how quality of chronic care stimulates productive interactions between patients and professionals.